Experimental analysis to determine the relationship between noise and back pressure for muffler design – Part I: Muffler design requirements - Mohiuddin, A. K. M. (IIUM Press, 2011)
This chapter describes part of the detailed methodology of relationship between noise and back pressure for muffler design. Starting with a brief introduction, an attempt is made here to present different steps of muffler design considering the relation between noise and back pressure. The design ofthe muffler chamber separation and arrangement is essential in determining the muffler characteristics. Some design considerations are proposed in order to come up with an optimum muffler design.